Quality of CRM Systems: a systematic mapping study - Boarim, Jhonatan; da Rocha, Ana Regina C. (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2019: Anais do XVIII Simpósio Brasileiro de Qualidade de Software, 2019)
CRM (Customer Relationship Management) is a term used in the industry to designate approaches, methodologies, software or internet resources that support a company to manage relationships with its customers in an organized way, integrating business processes, sales, customer service, marketing, field services and other functions that affect customers. These systems are complex and have specific quality characteristics. The ISO/IEC 25000 family of international standards defines general software quality characteristics but does not cover all the quality characteristics required for specific software products. This paper presents a systematic mapping study that tried to identify in the technical literature quality characteristics of CRM Systems.